Neonatal acute kidney injury: recording rate, course, and outcome: one center experience. (18th October 2019) - Cleper, Roxana; Shavit, Itay; Blumenthal, Danit; Reisman, Lewis; Pomeranz, Galit; Haham, Alon; Friedman, Shiran; Goldiner, Ilana; Mandel, Dror
Abstract: Background: Neonates, and particularly preterm newborns, are at increased risk for acute kidney injury (AKI) due to immature kidney function. While specific criteria have been defined for AKI in this particular population, this diagnosis is frequently overlooked, and consequently, is often not recorded in patients' medical files. AKI-associated short- and long-term morbidity and mortality underline the importance of this diagnosis Objective: To assess the recording rate of AKI in the neonatal intensive care unit (NICU), and to identify clinical features that may promote awareness to this condition. Study design: The database of one medical center was searched for serum creatinine values above 1 mg% among all the newborns (more than 48 hours old) who were hospitalized in the neonatal intensive care unit (NICU) during the years 2010–2015, and who underwent at least two blood tests during their hospitalization. The files of patients who met acute kidney injury (AKI) diagnostic criteria were searched for AKI diagnosis, maternal, fetal, and postnatal course and outcome. Results: Of 59 newborns who met AKI criteria, 51 (86%) were preterm and 8 term newborns. The respective mean gestational weeks at birth were: 28 ± 3 and 38.5 ± 1, and mean birth weights: 1002 ± 57 and 3157 ± 375 grams. Mortality rates were 14/51 (27%) versus 1/8 (12.5%). Of the 44 survivors, AKI was recorded in the medical files of 9/37 (24%) preterm versus 5/7 (71%) term-newborns. AKI associated with twin pregnancy in preterm neonates: 22 (43%) versus 1 (12.5%) in term-newborn. Unexpected high frequencies of maternal obstetrical problems and cesarean section delivery: 62.5 and 78%, respectively, along with persistently depressed 5-min Apgar 6.6 ± 3.5 were found in term newborns with AKI. Congenital anomalies of the urinary tract (CAKUT) were suspected prenatally on fetal ultrasound in 3 (6%) and 1 (12.5%) of the respective groups, a 10-fold higher rate than that observed in the general population. AKI recurred in 18 (35%) of the preterm and none of the term neonates. Mild AKI episodes (Stage 1–2) occurred in 30/37 (81%) by contrast to severe events (Stage 3) in 4/7 (57%) preterm and term survivors, respectively. Ventilation duration associated significantly with AKI recurrence, and sepsis with mortality: OR 1.25 (95%CI = 1.09–1.43) ( p  < .001) and OR = 4.65 (95%CI = 1.26–17.2) ( p  = .014), respectively. Conclusions: We demonstrated underreporting of AKI, particularly among preterm newborns, a population at high risk of developing recurrent episodes. Our data suggest different clinical profiles of AKI among preterm and term neonates: with later onset, milder but recurrent episodes in the former. Increased alertness for AKI diagnosis is needed for neonates with prolonged respiratory support, treated with diuretics and after sepsis. Newborns suspected of CAKUT (Congenital Anomalies of Kidneys and Urinary Tract) as per fetal ultrasound might need closer observation for AKI occurrence.